2009
DOI: 10.5951/mtms.14.9.0532
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solving and the English Language Learner

Abstract: Various techniques can enhance mathematics instruction for English language learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…For example, some students in Teacher B's class interpreted kiwi birds as kiwi people. The findings concur with those of Brown et al (2009) and Sharma (2014). Brown et al (2009), who argue that when students are faced with contexts that are unfamiliar, it can hinder their ability to understand what is being asked of them.…”
Section: Using Real-life Contextssupporting
confidence: 85%
See 1 more Smart Citation
“…For example, some students in Teacher B's class interpreted kiwi birds as kiwi people. The findings concur with those of Brown et al (2009) and Sharma (2014). Brown et al (2009), who argue that when students are faced with contexts that are unfamiliar, it can hinder their ability to understand what is being asked of them.…”
Section: Using Real-life Contextssupporting
confidence: 85%
“…Collaborative work allowed the students to collaborate in their learning and ties in with the work of Brown et al (2009) and Schleppegrell (2011), who explain that when language learners work alongside a partner, they are given the opportunity for interaction and support to enhance their learning. Schleppegrell (2011) reported that collaboration can afford language learners the chance to ask questions and make mistakes in a safe setting in which they can receive direct and immediate feedback.…”
Section: Collaborative Learningmentioning
confidence: 99%
“…Furthermore, the use of physical resources or pictures can support students in their comprehension of statistical terms (Brown et al, 2009;Nguyen & Cortes, 2013). One fundamental word in statistics that has lexical ambiguity for students is "random" (Kaplan et al, 2014).…”
Section: Using Non-linguistic Cuesmentioning
confidence: 99%
“…Collaborative learning is a powerful tool for all students, but especially ELL (Takeuchi, 2016). When ELL can work alongside a partner, they are given the opportunity for interaction and support, enhancing their learning (Brown et al, 2009). Collaboration affords ELL the chance to ask questions and make mistakes in a safe setting, where they can receive direct and immediate feedback.…”
Section: Collaborative Learningmentioning
confidence: 99%
“…This means that to appropriate meanings in mathematical language is also similar to how context functions in linguistic operations. Also, Brown, Cady & Taylor (2009) emphasize that ML syntax and semantics are a precise form of short cut in representing meanings in Mathematics, and to make them sensible is to understand contexts and conventions.…”
Section: Review Of Related Literaturementioning
confidence: 99%